Review: Analisis Kestabilan Lereng dengan Metode Analisis Balik Menggunakan Data Perpindahan Terukur - Sumbung, Dwi Yolanda (ReTII, 2022)
Slope monitoring is an important geotechnical aspect and becomes a basic component for planning the efficient and safety design. Various monitoring instruments have recently been implemented in the mining industry. Interpretation of the slope monitoring results such as measured displacements have been used in the back analysis method that applied by Sakurai, et al in 1987 with the application of numerical methods. For this reason, this paper provide an overview of slope stability back analysis using measured displacement data based on various previous studies.